Three-Year Variability Of Energy And Carbon Dioxide Fluxes At Clear-Cut Forest Site In The European Southern Taiga - Vadim V. Mamkin; Yulia V. Mukhartova; Maria S. Diachenko; Julia A. Kurbatova (Geography, Environment, Sustainability)
Forest  clearing  strongly  influences  the energy,  water and greenhouse  gas exchange at the land sur face - atmosphere inter face. To estimate effects of clear cutting on sensible (H), latent heat (LE) and  CO2 fluxes the continuous eddy covariance measurements were provided at the recently clear-cut  area situated in the western  part of Russia from spring 2016 to the end of 2018. The possible effects of surrounding  forest on the air flow disturbances and on the spatial pattern of horizontal advection terms within the selected clear-cut area were investigated using a process-based 3D momentum, energy and CO2 exchange  model.  The modeling  results showed a very low contribution  of horizontal advection term into total turbulent momentum  fluxes at flux tower location in case of the southern wind direction. The results of field flux measurements  indicated  a strong inter- and intra-annual  variability of energy and CO2 fluxes. The energy budget is characterized by higher  daily and monthly   LE fluxes throughout  the entire  period  of measurements excepting the first two months after timber harvest. The mean Bowen ratio (β=H/LE) was 0.52 in 2016, 0.30 - in 2017 and 0.35 - in 2018. Analysis of CO2 fluxes during the first year following harvest showed  that the monthly CO2 release at the clear-cut area consistently exceeded the CO2 uptake  rates. The mean net ecosystem  exchange  (NEE) in the period was 3.3±1.3 gC∙m-2∙d-1. During the second and the third years of the flux measurements the clear-cut was also a prevailed sink of CO2 for the atmosphere excepting short periods in June and in the first part  of July when daily CO2  uptake was higher than CO2  release rates. The mean NEE rates  averaged   for  the entire warm period of corresponding  years were 1.2±2.3  gС∙m-2∙d-1 in 2017 and 2.8±2.5  gC∙m-2∙d-1 in 2018, respectively.  The mean ratio between  gross  primary  production  (GPP) and ecosystem  respiration (TER) was 0.58 in 2016, 0.84 - in 2017 and 0.74 - in 2018.